2021
DOI: 10.7717/peerj-cs.517
|View full text |Cite
|
Sign up to set email alerts
|

A new secure authentication based distance bounding protocol

Abstract: Numerous systems are being employed in daily life where two entities authenticate each other over a range of distance. The distance involved is relatively small, but still attacks were documented. The distance bounding (DB) protocol was introduced to cater to security requirements. The schemes, however, are still prone to several threats; mainly the Relay Attack (Terrorist and Mafia Fraud). In Mafia Fraud, an attempts are made to get accepted as the prover either by replaying of messages or by the help a malic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
(94 reference statements)
0
1
0
Order By: Relevance
“…[9,10] utilized quantum bits and proposed more secure and efficient DB protocols for RF systems. Comprehensive reviews on distance-bounding protocols can be found in recent studies such as [11,12]. However, DB-based methods may suffer from an imprecise distance estimation due to the short RFID/NFC communication distance and the fast signal propagation speed.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] utilized quantum bits and proposed more secure and efficient DB protocols for RF systems. Comprehensive reviews on distance-bounding protocols can be found in recent studies such as [11,12]. However, DB-based methods may suffer from an imprecise distance estimation due to the short RFID/NFC communication distance and the fast signal propagation speed.…”
Section: Introductionmentioning
confidence: 99%